Differential Proliferative Characteristics of Alveolar Fibroblasts in Interstitial Lung Diseases: Regulative Role of IL-1 and PGE2 - Elizabeth Fireman; Shlomo Ben Efraim; Joel Greif; Hava Peretz; Shmuel Kivity; Marcel Topilsky; Yosef Rodrig; A. Yellin; Ron N. Apte (Mediators of Inflammation)
Fibroblasts (Fb) from patients with sarcoidosis (SA) and hypersensitivity pneumonitis (HP) exhibited a lower proliferative capacity compared with Fb obtained from control (CO) and diffuse interstitial fibrosis patients (DIF). Proliferation of Fb from SA or lip patients was suppressed by autologous LPS-stimulated alveolar macrophages (AM) supernatants but not by those from CO patients. Similarly, alveolar macrophages (AM) derived supernatant, obtained from CO, did not suppress the proliferation of SA and HP Fb. AM from SA and HP patients secreted higher amounts of IL-1α and β compared with controls and compared with Fb from SA and HP patients. Steady levels of IL-1α and βmRNA were expressed in unstimulated and stimulated cultures. Fb from SA and HP patients could be stimulated by LPS to secrete significantly higher levels of PGE2 than those detected in supernatants from LPS stimulated Fb of DIF patients. Only the proliferation of Fb from SA and HP patients was sensitive to amounts of IL-1 equivalent to those detected in the lung of these diseases. As SA and HP are two diseases where irreversible deterioration occurs in only 20% of the patients, we hypothesize that mediators in the lung may modulate Fb proliferation. IL-1 of AM origin and PGE2 of Fb origin secreted at high levels, may be candidates for this suppression because it was abrogated by anti IL-1β and indomethacin.